Enhancing Sharia Financial Inclusion in Rural Areas: Integrating Service Quality, Technological Innovation, and Financial Literacy in Baitul Maal Wat Tamwil - Al Hadi, M Qoshid; Wijayanti, Dwi Marlina (Likuid Jurnal Ekonomi Industri Halal, 2026)
Sharia financial inclusion (SFI) plays a crucial role in promoting equitable economic development, particularly in rural areas where access to formal financial services remains limited. This study examines the integrated effects of service quality, financial literacy, and technological innovation on SFI among active Baitul Maal wat Tamwil (BMT) customers in rural South Kalimantan, Indonesia, while assessing whether socio-economic status moderates these relationships. Using survey data and Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings show that financial literacy and service quality have significant positive effects on SFI, underscoring the importance of customers’ capability readiness and the quality of institutional interaction in fostering participation. Technological innovation shows no significant direct effect, suggesting that digital or technological initiatives alone may be insufficient without adequate literacy and service support. Additionally, socio-economic status does not significantly moderate the proposed relationships, indicating that the positive roles of literacy and service quality are relatively consistent across socio-economic groups. The study contributes by offering an integrated empirical model of key drivers of sharia financial inclusion in rural Islamic microfinance and provides practical insights for BMTs and policymakers to prioritize service improvement and financial literacy development to strengthen sustainable SFI.